The DEVELOPMENT OF CHARACTER STRENGTHENING IMPLEMENTATION GUIDELINES FOR STUDENTS: Case research : Students of the Faculty of Education, The State University of Makassar - Erma Suryani Sahabuddin; Abdul Haling; Nurlita Pertiwi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
Character is the values of goodness that have become a habit in action, which is a person's personality formed as a result of applying the various virtues. Character is a good mental trait that is shown when behaving politely, generously, forgiving, full of love, willing to sacrifice, appealing to humor, not excessive, and always obedient and pious. Character education focuses on implementing good values either in actions or behavior. Thus, character education is a process of forming habits in applying good values including the formation of moral knowing, moral feeling, and moral action. This research aims to develop a guidebook for implementing the strengthening of character education to solve moral dilemmas for students. The developed guidebook is expected to have validity and practicality in instilling good values for students. The research type is research development. The subjects of this research consisted of value education experts, lecturers, and students. Data were obtained by using interviews, documentation, and questionnaire techniques. Data analysis techniques used qualitative and quantitative analysis. The results showed that the character values for developing a guidebook for strengthening the character education consisted of five main characteristics, including behavior, diligence, cleanliness, neatness, and discipline. Additionally, those characteristics can be applied through intra-curricular, co-curricular, extra-curricular, and non-curricular activities. The test results of the guidebook were valid, and the results of the responses from prospective users showed that the Graduate Competency Standards, Content Standards, and Program Descriptions and assessment were in highly great qualifications. The results of this research were expected to meet the demands of providing a guidebook for strengthening the character education that can be used by lecturers and students in the implementation of strengthening of the character education at the Faculty of Education, The State University of Makassar. Keywords: Development research, Guidebooks, Strengthening Character Education, Students